Dynamics of development of the economic relations between Georgia and USA in 2003-2013 - Chakhoyan, Edgar (YSU Journal of International Affairs, 2021)
The article is dedicated to the study of the dynamics and ways of developing Georgia-US economic relations during the presidency of Mikheil Saakashvili in Georgia. The motives for the formation and strengthening of close economic relations between the parties are discussed in details, as well as the success achieved as a result of the frequent meetings of senior officials of the two countries. US Presidents George W. Bush's and Barack Obama's administrations' foreign economic and political approaches to Georgia, especially since the Rose Revolution in 2013, have been explored and studied. The role and significance of the bilateral documents on financial and economic relations signed between the parties were analyzed. Various facts have been observed that have hampered the multifaceted and balanced development of the Georgian economy. Particular attention is paid to the development of the economic relations between Georgia and the Russian Federation. The article also provides a comparative analysis of the volume of trade turnover (export and import) by year.
Keywords: Georgia’s economy; sustainable development; US support; bilateral agreement; black market; energy corridor; South Caucasus; Russian Federation; economic relations; free trade; Silk Road; Millennium Challenges; West-Asia crossroad; trade turnover